Perlindungan Anak Yang Terlantar atau Beresiko Dari Kekerasan Seksual - Ayang Audita Siregar; Asri Vivi Yanti Sinurat; Hikmat Syahputra Tarigan; Ari Dermawan; Dhiny Safryda Rawy (Cattleya Darmaya Fortuna, 2025)
This study applies a normative juridical legal approach. In Indonesia, cases of violence against children often occur, such as abuse and sexual harassment. This situation of course creates difficulties because it can damage the mental condition of the child. Of the various types of sexual harassment and abuse, the greatest impact occurs on the mental and emotional damage of the child victims. Sexual abuse of children is an example of a human rights (HAM) violation, particularly concerning children's rights (right of child). Up to now, many regulations have been created to protect children from acts of sexual violence.